IKLAN POLITIK DI MEDIA ONLINE DAN PEER GROUP TERHADAP KEPUTUSAN MEMILIH PARA PEMILIH MUDA PADA PEMILIHAN PRESIDEN 2019 - Dian Marhaeni Kurdaningsih,; Urip Mulyadi, (Mediakita, 2019)
Young voters are very close to online life. Advertising as part of online media products should be able to provide knowledge and change attitudes to the audience. Likewise, peer groups or playing groups. The behavior of young voters will be greatly influenced by their peer group. And as peer group students can point to groups of friends to discuss, friends who can communicate with each other and understand each other among its members. How advertisements in online media and the role of peer groups influence the decisions of young voters. This research intends to prove the uses and gratification theory that audiences will seek and select media content to fulfill their interests in seeking presidential candidacy information. The theory is also supported by social conversation theory. The research methodology uses the Kendall analysis in which this analysis requires a significant and positive relationship to the variables. The analysis shows that there is a positive and significant relationship with sufficient results obtained between advertisements in online media on voting behavior and peer groups on the knowledge of voting for young voters. The conclusion of this research is that online mass media is very much a reference for young voters in gaining knowledge about candidates. The role of peer groups in students in the Semarang community is still strong. The idea recognition model will be more effective utilizing this peer group. This research is still far from perfect, the accuracy of the data because the selected variables are very limited so the relationship between variables needs to be supported by accurate supporting variables. This deficiency can be added to further research by adding or proving separately the groupthink theory and the muted theory.